Urban Photography/Cultural Geography: Spaces, Objects, Events. Issue 3 (March 2014) - Hunt, Mia A.
Abstract Image‐making is bound up in our experience of urban space. In artistic and academic practice, contemporary urban photography has critically reworked street photography traditions, embracing its energy and spontaneity, while inviting a more dialogic and reflexive approach. Although the use of urban photography has been somewhat limited in cultural geography research, the practice has enormous potential to complement and enhance contemporary enquiries in the field – particularly those that highlight feelings, experience, and textures of place and draw from more‐than‐representational approaches. A return to making urban photos also chimes with the current approaches that incorporate creative practice and performative methodologies to introduce uncertainty into research. Here, I consider what cultural geographers might gain by exploring city spaces, objects, and events through the lens. I focus not on the images themselves, but on the practice of doing urban photography and on what these images may do for research. In particular, photography may help evoke the feeling of place and its material richness. By focusing on urban microgeographies and by opening work to ambiguity and chance, geographers may create new space for interpretation. Attending to material with the camera also enables us to play with value and hierarchy and provokes the animation and agency of matter. Finally, as well as highlighting the matter of things, images can capture the matter of our own bodies caught up in events with the cities we inhabit. Urban photography offers a way of doing research that opens up city spaces, objects, and events, so we can better reflect on the complex textures, feelings, and experiences of urban space.